Usability Evaluation Experiment of 3D User Interfaces for Elderly (Revista Brasileira de Computação Aplicada, 2019)
Health professionals have used 3D user interfaces as support tools for the elderly rehabilitation, offering fun and beneficial resources for the practice of physical and cognitive activities to them. In this context, it is necessary to establish mechanisms to evaluate the usability of these interfaces, in order to achieve a balance between functionality, ease of use and sense of well-being. The aim of this study is to report a usability evaluation experiment of a virtual reality game developed specifically to elderly people, as a means to identify the needs of this public regarding 3D user interface evaluation. An initial methodology was tested exploring two points of view in the game, and its results showed that it was adequate for seniors. However, it was noted the need to include training periods and an evaluation with a heterogeneous group of seniors to consolidate and optimize the proposed approach, as well as readjust the instruments used.